2020
DOI: 10.24018/ejfood.2020.2.5.114
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Effect of Land Preparation Methods and Weeding Frequency on Seasonal Soil Properties and Maize Yield

Abstract: Dynamics of soil physical properties and maize yield were investigated in both major and minor cropping seasons under different land preparation methods and weeding frequency. A factorial design experiment was organized on a randomized complete block design with three replicates. The land preparation methods were plough + harrow (P + H) and no-tillage (NT) while weeding frequency treatments comprised 0, 1, 2 and 3-hoeing regimes. In both seasons, P + H yielded good penetration resistance and bulk density, high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…While tillage and weed control treatment permutations have not shown significant interaction effects on penetration resistance, results indicate that tillage with hoe treatment combinations presents lower resistance in the upper (0-15 cm) and middle (15-30 cm) layers in comparison with other permutations. Appah [37] has reported similar findings under maize cultivation and attributed the trend to marked surface disturbance by hoeing. Results obtained by Olaoye [72] while working in Ferric Luvisols in Nigeria confirm the lower penetration resistance under the ploughtill system confirmed in this study.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…While tillage and weed control treatment permutations have not shown significant interaction effects on penetration resistance, results indicate that tillage with hoe treatment combinations presents lower resistance in the upper (0-15 cm) and middle (15-30 cm) layers in comparison with other permutations. Appah [37] has reported similar findings under maize cultivation and attributed the trend to marked surface disturbance by hoeing. Results obtained by Olaoye [72] while working in Ferric Luvisols in Nigeria confirm the lower penetration resistance under the ploughtill system confirmed in this study.…”
Section: Discussionmentioning
confidence: 59%
“…While plough-till methods pulverise the soil surface, increase soil voids and encourage water admittance (as recognised by [37], moisture retention can be offset by the apparently little or no mulch cover and deep soil voids, which are flow-active, leading to moisture loss at upper layers through evaporation [61] and at greater depths by percolation. e higher moisture contents in no tillage and minimum tillage treatments with the lower layer in deep tillage is likely because of this phenomenon, a finding corroborated by Sharma et al [49] and Lui et al [62], although it is in contrast with those reported by Kurshid et al ( 2006), Khan et al [51] and Aikins and Afuakwa [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While intense ploughing under CT and weed control interactions pulverise and disrupt the soil surface, increase pore volume and permit water entry (as noted by Appah [60]), retention of moisture can be counterbalanced by the little or no residue retention and deep soil voids which are flow-active, leading to moisture loss by evaporation at the upper layers (15-30 cm) [61] and by percolation at deeper layers [62]. Our study corroborates the results reported by Abdollahi et al [63] who found higher soil moisture content in the middle layer (12-25 cm) of sandy loam soil on CsT and CT plots and ascribed the higher moisture content to better pore connectivity and higher pore volume, respectively, at that depth.…”
Section: Plos Onementioning
confidence: 99%
“…The direct and indirect effects of weed management, which can be both beneficial and bad, have an effect on soil health and crop productivity [ 44 ]. Soil surface disturbance differs under different tillage, hand weeding, and chemical control methods [ 45 ]. Much research have been conducted to assess the influence of tillage on soil physical properties and the effectiveness of infiltration models.…”
Section: 0 Introductionmentioning
confidence: 99%